Study of Mono and Di-O-caffeoylquinic Acid Isomers in Acmella oleracea Extracts by HPLC-MS/MS and Application of Linear Equation of Deconvolution Analysis Algorithm for Their Characterization - Maria Bellumori; Marco Pallecchi; Beatrice Zonfrillo; Luigi Lucio; Marta Menicatti; Marzia Innocenti; Nadia Mulinacci; Gianluca Bartolucci (MDPI AG, 2023)
Chlorogenic acids, the esters of caffeic and quinic acids, are the main phenolic acids detected in Acmella oleracea extracts and have gained increasing interest in recent years due to their important biological activities. Given their structural similarity and instability, the correct analysis and identification of these compounds in plants is challenging. This study aimed to propose a simple and rapid determination of the A. oleracea caffeoylquinic isomers, applying an HPLC-MS/MS method supported by a mathematical algorithm (Linear Equation of Deconvolution Analysis (LEDA)). The three mono- and the three di-caffeoylquinic acids in roots of Acmella plants were studied by an ion trap MS analyzer. A separation by a conventional chromatographic method was firstly performed and an MS/MS characterization by energetic dimension of collision-induced dissociation mechanism was carried out. The analyses were then replicated using a short HPLC column and a fast elution gradient (ten minutes). Each acquired MS/MS data were processed by LEDA algorithm which allowed to assign a relative abundance in the reference ion signal to each isomer present. Quantitative results showed no significant differences between the two chromatographic systems proposed, proving that the use of LEDA algorithm allowed the distinction of the six isomers in a quarter of the time.